Ritual transformation and socio-political change in an Andean peasant community - Guillet, David W. (1974)
The general festival system is one of the most effective integration mechanisms in rural life in the Andes (Martínez 1959, Mangin 1961). The term "festival system" covers a great diversity of ritual activities including non-religious factors of socialization, dances and the ritual exchange of food and drink, as well as religious elements taken from Catholic practices, such as the celebration of mass, the procession and some individual rites. According to Dewey (1970) the party system can be classified into two types of ritual activities: a) those of an individual nature centered on the person and that mark the important stages of the life cycle: Birth, first communion, marriage and death; and b) those that are centered on the group, aimed at highlighting and expressing the identity of the community.